Laughter and Violence:: pedagogical approaches to clowning in university Theater studies - Consentino, Marianne (Revista Brasileira de Estudos da Presença, 2025)
This article seeks to analyze possible relationships between comicality and violence. The study was developed through theoretical-practical research, whose procedures involved bibliographical research through scenic experimentation laboratories, carried out with students from the Theater Licentiate Degree course, at the Federal University of Pernambuco. The rapprochement between clowning and the universe of popular culture was explored, especially considering the concept of grotesque realism proposed by Bakhtin. The necessity of violence as a pedagogical resource in the proposed technique was problematized and it was concluded that the learning of this technique requires the establishment of an environment of trust, play and freedom among students.